Supercorp how vanguard companies create innovation, profits, growth, and social good - Kanter, Rosabeth Moss (Crown Business, 2009)
Discusses the concept of "vanguard companies" whose mission combines a social conscience along with the ability to deliver on customers' needs better than competitors, citing IBM's expertise in India following the 2006 tsunami and earthquake as an example.